Secure Multicast Communications in Cognitive Satellite-Terrestrial Networks - Xiong, Jun; Ma, Dongtang; Zhao, Haitao; Gu, Fanglin (IEEE communications letters, 2019)
This letter studies a secure multicast transmission design for cognitive satellite-terrestrial networks with multiple multi-antenna eavesdroppers, where the satellite (SAT) delivers a common confidential message to a group of legitimate users and the interference from the terrestrial base station (BS) is utilized to strengthen the security of the satellite link. Our goal is to minimize the total transmit power, subject to the secrecy rates for the satellite links as well as the information rate for the terrestrial link. The resulting optimization problem involves the joint optimization of the information covariance matrices at the SAT and the BS, which is non-convex and challenging. We have introduced a successive convex approximation method to transform the non-convex constraints into linear ones and proposed an effective iterative algorithm. Simulation results demonstrate the superiority of the proposed algorithm.